STRATEGI PENINGKATAN PRODUKTIVITAS PADI DI DESA PADACENGA: LANGKAH MENUJU KESEJAHTERAAN MASYARAKAT - Idris, Muhammad (Penerbit Widina, Widina Media Utama, 2024)
Rural agricultural development is an inseparable unit. Agriculture is the main component that supports rural life. However, the role of the agricultural sector as a whole has not developed so that it has not succeeded in raising the position of farmers to a prosperous level as expected. The role of the agricultural sector is faced with problems in line with the development of the rural economy. A strategy for future development of the agricultural sector is needed, through various conducive policy agendas, so that the role of the agricultural sector in the rural and national economy can be increased. The approach used in this research is the Socialization approach. So KKN students at Muhammadiyah University of Bone carried out socialization in an open way. The author gathered farmers in Padacenga village to find out information related to strategies for improving lowland rice farming to produce high and good rice production in order to improve the economy of village communities through supporting data sourced from research journals, both national and international. This literature study has the aim of formulating strategic priorities in developing lowland rice farming businesses which have an impact on improving the economy in Padacenga village, including processing paddy fields and paddy fields, increasing the availability of quality rice and increasing the availability of quality seeds, increasing the rice planting index, increasing farmers' income.ABSTRAKPembangunan pertanian di pedesaan merupakan satu kesatuan yang tidak dapat dipisahkan. Pertanian merupakan komponen utama yang menopang kehidupan pedesaan. Namun demikian, peranan sektor pertanian secara keseluruhan belum berkembang sehingga belum berhasil mengangkat posisi petani ke tingkat sejahtera seperti yang diharapkan. Peranan sektor pertanian dihadapkan pada permasalahan seiring dengan perkembangan ekonomi pedesaan. Diperlukan strategi pengembangan sektor pertanian ke depan, melalui berbagai agenda kebijakan yang kondusif, agar peran sektor pertanian dalam perekonomian perdesaan dan nasional dapat ditingkatkan. Pendekatan yang digunakan dalam penelitian ini adalah pendekatan Sosialisasi. Jadi mahasiswa KKN Universitas Muhammadiyah Bone melakukan sosialisasi dengan cara terbuka. Penulis mengumpulkan para petani di desa Padacenga untuk mengetahui informasi terkait strategi peningkatan pertanian padi dataran rendah untuk menghasilkan produksi padi yang tinggi dan baik dalam rangka meningkatkan perekonomian masyarakat desa melalui data-data pendukung yang bersumber dari jurnal-jurnal penelitian baik nasional maupun internasional. Studi literatur ini memiliki tujuan untuk merumuskan prioritas strategi dalam mengembangkan usaha tani padi dataran rendah yang berdampak pada peningkatan perekonomian di desa Padacenga, antara lain pengolahan lahan sawah dan lahan ladang, peningkatan ketersediaan beras berkualitas dan peningkatan ketersediaan benih berkualitas, peningkatan indeks pertanaman padi, peningkatan pendapatan petani.